EUROPEAN EXPERIENCE IN THE DEVELOPMENT AND PROMOTION OF BUSINESS TOURISM IN THE TOURISM SPHERE OF UKRAINE (Development Service Industry Management, 2023)
The article analyzes the development and promotion of business tourism in Ukraine. The experience of European countries is analyzed. Nowadays, business or business tourism is becoming more and more relevant in the field of tourism. This type of tourism allows you to find the necessary connections, acquire important knowledge, invaluable experience and skills necessary for the development and growth of business, increases the level of qualification and professionalism. Business tourism is a type of modern, rapidly developing tourism. The development of business tourism is characterized by the increasing interest of business people from all over the world in Ukraine. This is one of the promising and profitable types of tourism. World globalization poses the task of increasing competitiveness and determining new priorities for the development of the economy in the tourism sector. Today, tourism is developing dynamically and, business tourism in particular, is becoming the main sphere of the world economy. Ukraine is not an exception in the participation of globalization processes, therefore there is a need to study international tourism.In Ukraine, business tourism began to develop quite quickly and reached a high level. Today, the country has many worthy places for holding business meetings and events of any scale and level. These are standard and non-standard locations of various capacities for all types of business events, different opportunities and budgets.In Ukraine, business tourism began to develop quite quickly and reached a high level. Today, the country has many worthy places for holding business meetings and events of any scale and level. These are standard and non-standard locations of various capacities for all types of business events, different opportunities and budgets. The necessary infrastructure for business tourism has also been created in the country: a specialized hotel base has been developed in all regions of the country, which makes it possible to choose a business hotel of the right category, with a capacity for different numbers of participants and equipped with everything necessary for productive work and a full-fledged rest; a wide selection of exhibition complexes and conference halls with the latest technical equipment designed for different numbers of visitors; modern technologies make it possible for a businessman to conduct business regardless of his location; international electronic payment systems operate; thousands of international, all-Ukrainian and regional exhibitions covering all spheres of human activity take place annually in the country.
Keywords: business tourism; types of business tourism; development factors; the importance of business tourism; impact on the tourism industry; the world market of business tourism; development trends; development resources in Ukraine; tourism business; organization and functioning; problems of the development of business tourism in Europe; prospects development; involvement of European experience; tourism sphere of Ukraine